THE IMPORTANCE OF ISLAMIC PHILOSOPHY TO RESIDENCES OF THE HISTORICAL CITY OF MARGILAN (Academia Science Repository, 2023)
This article discusses the role of Islamic philosophy in the formation of settlements in the historical city center of Margilan, and gives practical suggestions for improving the foundations and methods of reconstruction of settlements.